Pengaruh Pendidikan dan Pelatihan Jangka Pendek Sekolah Tinggi Penerbangan Indonesia Terhadap Kinerja Pegawai Bandar Udara Internasional Lombok Mataram - Satiti Utami; Rini Sadiatmi (Politeknik Penerbangan Indonesia Curug, 2020)
Advances in science and technology have a major influence on changes in systems and work tools in an organization. Work facilities supported by modern technology are expected to make it easier and faster in achieving organizational goals. However, in reality it is difficult to achieve what is expected, because any sophisticated means is not the only aspect that can facilitate efforts to achieve organizational goals.